Psychological aspects of top Croatian sprint runners: athletic engagement and athletic identity - Sindik, J.; Vesna, B.; Sasa, M. (Advances in sports research, 2015)
Athletic engagement and athletic identity are conceptually interrelated constructs. Athletic engagement (AE) is an enduring, relatively stable sport experience, which refers to a generally positive affect and cognition about one`s sport as a whole. The efficient role of athletic identity (the level of identification with the role of athlete) in realization of the athlete`s career goals could be observed in relation to the athletic engagement. Thus, first goal of this research was to determine the groups of participants (top Croatian sprint runners, active and retired), with respect to the different aspects of their athletic identity and athletic engagement, taking into consideration several relevant labeling variables: gender, status (active/retired), marital status, educational level, winning international medals in competitions or not. The second goal was to forecast winning medals on international competitions, based on the dimensions of athlete`s athletic identity and athletic engagement. The third goal was focused on determining the unique latent dimension of athletic engagement and athletic identity. The research was carried out on a sample of 71 top athletes-sprinters, active and retired, aged from 18 to 81, 27 (38%) females and 44 (62%) males, using the questionnaires Athlete Engagement Questionnaire (AEQ) and Athletic Identity Measurement Scale (AIMS). The results of K-means clustering revealed the characteristic profiles of the athletes, divided in two groups: sprinters with higher level in all dimensions of athletic engagement and athletic identity, as well as those with lower means in the same dimensions. In spite of the larger number of cases classified in the first cluster, relative distributions of cases in each cluster provide the information about several selected dependent variables (gender, etc.). On the other hand, in logistic regression, Cox & Snell`s R Square and Nagelkerke`s R Square were not statistically significant: thus, the forecasting of winning medals on international competitions based on predictors (dimensions of athletic engagement and athletic identity) was not statistically significant. Finally, unique second-order factor approximate all the dimensions of athletic engagement and athletic identity. The most reasonable explanation for these findings is given in terms of very similar psychological characteristics of top sprinters on the same level of sport excellence, as well as in terms of conceptually interrelated constructs, which are investigated. See discussions, stats, and author profiles for this publication at: https://www.researchgate.net/publication/287640936_Psychological_aspects_of_top_Croatian_sprint_runners_athletic_engagement_and_athletic_identity